Religious education in schools (2021)
Religious education has traditionally been part of school education in Latin American societies. Until less than twenty years ago, Christian, and specifically Catholic, education was dominant in the Colombian school system. Nowadays, and after multiple constitutional and legal changes, public debates about religious education in schools remain regarding the exercise of rights and freedoms and also as to the proper epistemological approach. Besides the Catholic Church, there are other actors who participate in this debate, who put forward legal, psychological and sociological perspectives. This article suggests that an inclusive religious education is a better formula than imposing one single doctrine, and recommends the creation of an open, pluralistic dialogue that takes into account the value of each person and his or her particular beliefs.